The Globe and the Disputes in Scene: Brizola and the Creation of An Emblematic Acronym, the Democratic Labor Party - Marcon, Marcelo (Revista Crítica Histórica, 2020)
This article aims research the way the newspaper O Globo elaborated its speech in the process of dispute for the domain of the acronym PTB (Brazilian Labor Party) between Leonel Brizola and Ivete Vargas, and the consequent creation of the PDT (Democratic Labor Party). This happened in the process of political opening of the Brazilian military regime and party reorganization. The way thar the newspaper elaborated its speech was analyzed according to the methodology proposed by Patrick Charaudeau. The analyze of the sources, the historiography and the methodology proposed, we understand that O Globo supports Ivete Vargas and invested in the politic disqualification of Leonel Brizola, once that the newspaper and the political from Rio Grande do Sul had different visions about the future of the politic in Brazil.